PP2A Phosphatase as an Emerging Viral Host Factor - Barski, Michal Slawomir; Minnell, Jordan James; Maertens, Goedele Noella (Frontiers in Cellular and Infection Microbiology, 2021)
Protein phosphatase 2A (PP2A) is one of the most ubiquitous cellular proteins and is responsible for the vast majority of Ser/Thr phosphatase activity in eukaryotes. PP2A is a heterotrimer and each of its subunits can be targeted by viral proteins to hijack and modulate its activity and downstream signaling to the advantage of the virus. Binding to PP2A is known to be essential to the life cycle of many viruses and seems to play a particularly crucial role for oncogenic viruses, which utilize PP2A to transform infected cells through controlling the cell cycle and apoptosis. Here we summarise the latest developments in the field of PP2A viral targeting; in particular recent discoveries of PP2A hijacking through molecular mimicry of a B56-specific motif by several different viruses. We also discuss the potential as well as shortcomings for therapeutic intervention in the face of our current understanding of viral PP2A targeting.